Why should I tell you? Applying a culturally attuned privacy theory to understand global customers' online disclosure behaviours in e-commerce transactions. (13th August 2009) - Zakaria, Norhayati; Zakaria, Nasriah; Yusof, Shafiz Affendi Mohd
This paper explores the effect of cultural values and information privacy concerns on the online disclosure behaviours of global customers engaged in e-commerce activities. Hence, the general research question is as follows: In what ways do cultural values and privacy induce or deter online disclosure behaviours? To understand online disclosure behaviours from the cultural and privacy perspectives, the paper draws on two theoretical frameworks. Hall's (1976) high-context/low-context cultural theory illuminates how cultural values induce or discourage disclosure behaviours and Petronio's (2002) Communication Privacy Management (CPM) theory is useful in explaining the psychological boundaries between disclosure and privacy. Integrating these two theories offers a culturally-attuned privacy theory to understand online disclosure behaviours. Finally, the paper provides perspectives on the implications for e-commerce in its efforts to attract global customers.